Teacher's Training on Classroom Instructional Design - Anggraini, Dita Rizki (Global Expert: Jurnal Bahasa dan Sastra, 2024)
Realizing on the importance of administering a systematic plan prior to the teaching and learning process, teachers might be oriented to any instructional design or model in education. This article discussed on the teacher’s real experiences on preparing such systematic plan after participating at particular training. An interview with one of the teachers of English in one of Senior High School in Palembang was conducted. As the consideration to collect the data, the teacher selected has joined a classroom-instructional-design training before. The results of the interview showed that most of the aspects of classroom instructional design are given during the training. In addition, the five components of learning as well as the procedure in designing the instruction were well given. The guidance and materials given on the training were believed to be that beneficial on the implementation of teaching and learning process. Keywords: Classroom instructional design, Instructional design model, Teacher’s training